A numerical investigation to determine longitudinal dispersion coefficient in ideal and randomized reticulated porous structures using transient direct pore level simulation. (15th June 2023) - Rambabu, S.; Parthasarathy, P.; Ratna kishore, V.
Highlights: Numerical estimation of longitudinal dispersion in reticulated porous media. Peclet number correlation using strut diameter as Characteristic length is proposed. Modified Peclet numbers of Kelvin structure are validated with literature data. Abstract: The purpose of this numerical investigation is to characterize the longitudinal dispersion coefficients in open-cell reticulated porous structures. Open-cell foams are modelled using idealized Kelvin cell structures. Using the conventional Navier–Stokes equation, airflow has been calculated through various porous structures. Along with the flow, the dispersion of a tracer fluid is traced across the structures and analyzed in terms of the effective dispersion coefficient. Using direct pore level simulations (DPLS), a parametric study is performed to understand the influence of geometrical parameters on the dispersion in porous media. To evaluate the longitudinal dispersion coefficient (LDC), the analytic solution gradients were fitted into the simulated gradients. From the results, a new characteristic length correlation is proposed to calculate the Peclet number, and it is compared with experimental and numerical data that are available in the literature.